Pelatihan Pembuatan Sabun dari Minyak Jelantah sebagai Upaya Pemanfaatan Limbah Rumah Tangga - Ismi Nurlatifah; Dine Agustine; Dadang Sujana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
During the pandemic, we are getting more demanded to maintain cleanliness and wash our hands frequently. The purpose of this community service activities is to educate the public in processing cooking oil waste into a useful product, that is soap. This activity is carried out as an effort to support the government program namely 5 M, which is one of the activity from this program is washing hands with soap. This activity was carried out in Tegal Kunir Kidul Village, Mauk Sub-District, Tangerang District. The methods that we used are workshops and direct mentoring. The participants who attended the workshop were 30 persons, consisting of program at village level womens and youth organizations. The results obtained from this workshop are the increasing of resident’s insight in terms of processing waste, as well as increasing skills in making soap products from cooking oil waste. In the future, it will not only come to waste processing, but also making the opportunities to increase businesses that can be manage by local villages.